A COLLECTION OF SURVEYS ON MARKET EXPERIMENTS. (30th March 2013) - Noussair, Charles N.; Tucker, Steven; Tucker, Steven; Noussair, Charles
Abstract This paper highlights the contributions in this special issue to the very large and rapidly growing research on experimental markets. It contains ten surveys of different streams of research in this area including asset markets, contests, environmental policy, frictions, general equilibrium, labor markets, multi‐unit auctions, oligopoly markets, and prediction markets.